The reaction of bisulfite with liposomal membranes. Issue 5 (October 1988) - Finch, L.; Southerland, W. M.
Abstract : Bisulfite has been shown to induce leakage of encapsulated substances from liposomal vesicles. The bisulfite induced leakage of either DNP-tyrosine, potassium ferricyanide, or [ 3 H]glycine was observed to be greater with lipsomes composed of phospholipids containing unsaturated fatty acids. The leakage of encapsulated substances from liposomes was found to be concentration dependent when incubated for a constant time interval and time dependent when incubated at a constant bisulfite concentration. In addition, bisulfite caused the leakage of approximately 5 times more [ 3 H]glycine from unilamellar liposomes than from multilamellar liposomes. These findings are consistent with the interaction of bisulfite with liposomal membranes via reaction with sites of unsaturation.